EFL Teachers’ Practice in Teaching Learning Process through E-Learning: A Study of English Teacher in Border Area Sambas - Meutia Eka Tirtasary; Yohanes Gatot Sutapa Yuliana; Clarry Sada (Universitas Sarjanawiyata Tamansiswa, 2023)
This study was a qualitative descriptive study. The participants of this study were three English teachers in the Senior High School category in the Sambas Border Area. Observation, interview, and documents were the instruments of this study. As a result, the researcher found that the participants in Sambas Border Area used WhatsApp to teach the students in the learning process. Other applications were used but it was as additional materials. The participants got problems due to network problems and low interactivity. In conclusion, it is recommended for the participants in this study apply Online Quizzes, Interactive Demos, and E-learning games to be spirit and creative in the teaching-learning process through E-learning since it is found that the participants in this study manage the classroom by applying online discussion to teach.